Analysis Standard Safety Risk Operating Procedures of AirNav Indonesia Head Quarter - Martha Saulina (Budapest International Research and Critics University, 2022)
Indonesia is one of the southeast Asian countries which consists of 17.504 islands separated by water. Realizing it, Government has open access so the world could see Indonesia's potential tourism through cooperation between the Ministry of Tourism and Ministry of Transportation (by optimizing hundreds of Airports and company private airports throughout Indonesia) and the Ministry of State-Owned Enterprises (through Aviation Stakeholders such as Angkasa Pura Airport, Angkasa Pura II, and AirNav Indonesia), also Airlines. According to the data sourced from Angkasa Pura II, throughout the year 2017 Soekarno- Hatta as the biggest Airport in Indonesia accommodated 63.015.620 domestic and international passengers or increasing 8% compared with the year 2016 which amounted to 58.195.484 passengers. This growth must be supported by well-systemized land and airside infrastructures which prioritize safety starting from preparation to its implementation, in this thesis intern focuses on safety in Air Navigation Services. Starting from the year 2013, the operation of Air Navigation Services is fully delegated to Perum LPPNPI then called AirNav Indonesia. Safety Management System Manual (Doc. 9859) as ICAO Document has been adopted by Indonesia to achieve safety in every aspect of aviation including Air Navigation Services. In this thesis, the intern focuses on the 2nd pillar of SMS – Safety Risk Management applied in AirNav Indonesia. To achieve ALOS, AirNav Indonesia is in the progress of a proactive approach. To realize those things in the execution, it is necessary to build Risk Analysis Standard Operating Procedure which contains Hazard Mapping, Hazard Identification and Risk Assessment (HIRA), and BowTie method to analyze, these are essential things to be done before something occurs then to be implemented for all AirNav Indonesia Headquarter and its Branches.